Evaluation of L-Lysine fortified bulgar millfeed for finishing swine - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1971)
A growing-finishing ration that substituted 25% L-lysine fortified bulgar millfeed for 20% of the sorghum grain and 5% of soybean meal' (44%) gave weight gains and feed:gain ratios for finishing swine similar to those with the control ration. But pigs receiving rations with the 25% bulgar millfeed replacing 15% of the sorghum grain and 10% of the soybean meal gained significantly (P<.0l) slower and 25% less efficiently, so we did not evaluate using more than 25% of the bulgar mil1feed in rations for finishing swine.; Swine Day, Manhattan, KS, October 7, 1971
Keywords: Swine day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 181; Swine; Bulgar millfeed; L-lysine; Finishing pigs; Feed/gain ratio